Cross-task cue utilisation and situational awareness in simulated air traffic control. (January 2019) - Falkland, Emma C.; Wiggins, Mark W.
Abstract: Objective: To examine the role of cross-task cue utilisation in the acquisition of situational awareness during the initial stages of learning to operate an air traffic control simulation. Background: Cue-based associations are an important component of situational awareness, a construct that is necessary for skilled process control, where the location, movement, and direction of multiple targets needs to be managed. However, the potential for high levels of situational awareness is difficult to assess in the absence of exposure. Previous research suggests that cross-task cue utilisation predicts the acquisition of feature-event associations that form the basis of situational awareness Method: Sixty university students undertook an assessment of cue utilisation in the context of motor vehicle driving and subsequently engaged in an air traffic control simulation task. During the air traffic control simulation task, situational awareness queries were introduced based on the Situation Awareness Global Assessment Test (SAGAT). Results: The analyses revealed that participants who demonstrated relatively higher levels of cross-task cue utilisation also demonstrated greater performance on the SAGAT and achieved greater performance during the simulated air traffic control task. Conclusion: The outcomes suggest a relationship between cross-task cue utilisation and situational awareness, particularly at the initial stages of skill acquisition. Application: Assessments of cross-task cue utilisation may be used to distinguish the propensity for prospective trainees to acquire the situational awareness necessary for complex, process control tasks such as air traffic control.